Philosophy 167: Class 2 - Part 4 - Regiomontanus: Some Key Pre-Copernicus Publications in Astronomy. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Introduces Georg von Peuerbach and Regiomontanus (Johannes Mller von Knigsberg); discusses the project to print in the original Greek the whole of the Almagest, Euclid, Apollonius, and Archimedes.; Opening line: "All right, so now I'm back to what happened in Europe after 1450."; Duration: 7:22 minutes.; Segment: Class 2, Part 4.